Integrating Infiltration Facility to Urban Road Drainage - Yau Seng Mah, Darrien; Chiat Ng, Tze; Josep Putuhena, Frederik (International Journal of Engineering and Technology, 2018)
It is proposed to merge an infiltration facility to the conventional road curb system. Towards this end, a Storm Water Management Model (SWMM) is developed to explore the effectiveness of the proposed component at Riveria housing estate, Kota Samarahan, Sarawak. The findings show that the integration is effective in reducing peak runoff. The results indicate that a scenario of hollow infiltration trench achieves zero runoff, and a scenario of filled infiltration trench has a 43.6% reduction in runoff compared with existing road drainage condition. Furthermore, the hollow infiltration trench is found to be the best among all the given scenarios. The SWMM modelling results provide a tool to quantitatively measure the probable use of the proposed measures to improve the existing road drainage system.Â Â